Human Rights in Policing: The Past, Present and Future. Issue 3 (11th July 2019) - Poolman, Sarah; Wilshaw, Richard; Grace, Jamie
Abstract: This article seeks to demonstrate, largely from practitioners' perspectives, the growing evolution in understanding and implementation of meaningful human rights standards within the policing context. In the early 2000s, human rights were perceived and treated as a rather restrictive framework in UK policing. They are now more readily seen as a set of tools that guide and help the police to balance the views and interests of all parties to the criminal justice process. Human rights values enable police in the UK to better endeavour to do the right thing, 'without fear or favour'.